The impact of teaching-research conflict on turnover intention: cross-level interaction effect of justice climate - Siqi, Zhao; Hong, Wang (Frontiers in Psychology, 2023)
Research-based on the Job Demands-Resources theory (JD-R theory) has revealed a close relationship between teaching -research conflict and job burnout. However, there needs to be more investigation into the complex relationship between teaching -research conflict and turnover intentions from the perspective of this theory. To address these gaps, this study, grounded in the JD-R theory, explores the relationships among teaching-research conflict, career adaptability, justice climate, job burnout, and turnover intention. Data collected through an online survey involving 858 Chinese university teachers, and the analysis utilized a Multilevel Structural Equation Model (MSEM) with Maximum Likelihood (ML) estimation. The findings reveal that job burnout mediates the relationship between teaching -research conflict and turnover intention. Career adaptability plays a moderating role in the connection between job burnout and turnover intention. Furthermore, justice climate exhibits a cross-level interaction effect concerning the relationship between teaching -research conflict and turnover intention. These findings offer innovative strategies for mitigating and preventing faculty turnover intention.